(untitled) (Journal of Economic Research & Business Administration, 2016)
Nowadays the audit efficiency is one of the main types of the control of execution of the State Budget which carried out by the supreme bodies of financial control of foreign countries. This article is sanctified by press- ing questions of estimation of economy, efficiency and effectiveness of the use of budgetary facilities. Aims, methods and practical realization of audit efficiency, arising up here problems and ways of their decision, are investigated in the article. The feature of this article consists of that introduction of audit ef- ficiency in activity of foreign organs of state financial control, demanded corresponding changes in their organizational structures. In many coun- tries as Belgium, Great Britain, Denmark, Norway, Netherlands, Sweden, were created the special subdivisions on the audit efficiency.